The effect of rizatriptan, ergotamine, and their combination on human peripheral arteries: a double‐blind, placebo‐controlled, crossover study in normal subjects - Tfelt‐Hansen, Peer; Seidelin, Kaj; Stepanavage, Michael; Lines, Christopher (British journal of clinical pharmacology, 2002)
Aims  To compare the peripheral vasoconstrictor effects of ergotamine, rizatriptan, and their combination, in normal subjects. Methods  This was a double‐blind, four‐way, crossover study. Sixteen young male volunteers, selected as responders to the vasoconstrictor effect of 0.5 mg ergotamine i.v., were administered 10 mg oral rizatriptan, 0.25 mg i.v. ergotamine, 10 mg oral rizatriptan+0.25 mg i.v. ergotamine, and placebo. The vasoconstrictor effect on peripheral arteries was measured with strain gauge plethysmography up to 8 h after dosing. The 8 h assessment period was divided into two 4 h intervals to assess the immediate (0–4 h) vs sustained effect (4–8 h) of treatment. Results  For the 0–4 h interval, the decreases in peripheral systolic blood pressure gradients were: placebo (−1 mmHg [95% CI: −3, 1])<rizatriptan (−5 mmHg [95% CI: −7, −3])<ergotamine (−15 mmHg [95% CI: −16, −13])=rizatriptan+ergotamine (−15 mmHg [95% CI: −17, −13]). For the 4–8 h interval, the decreases were: placebo (−5 mmHg [95% CI: −8, −3])=rizatriptan (−8 mmHg [95% CI: −11, −5])<ergotamine (−26 mmHg [95% CI: −29, −24])=rizatriptan+ergotamine (−28 mmHg [95% CI: −31, −26]). Conclusions  In normal subjects, rizatriptan 10 mg orally had only a small transient vasoconstrictor effect on peripheral arteries compared with the sustained and more pronounced effect of 0.25 mg i.v. ergotamine. Furthermore, rizatriptan exerted no additional effect on ergotamine‐induced constriction of peripheral arteries when the two drugs were given in combination.